Kiprah Muhammadiyah dalam Pemberdayaan Masyarakat Desa - Ucin Muksin (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2015)
As a socio-religious organization that has a strong attention to the paradigm of education in the country, Muhammadiyah a mouthpiece for membuminya moral and ethics in society. For Muhammadiyah, education is not only to educate students and the community to be clever, but more importantly how the educational values integrated into the social and religious values. Departing from this fact, this study is directed to look at the lunge, the organization Muhammadiyah in District Bojonggede the